Stable Sn2+ doped FAPbI3 nanocrystals for near-infrared LEDs - Begum, Raihana (2020)
Herein, we report Sn2+ doping in FAPbI3 NCs to stabilize the α-phase, while using propionic acid as a co-ligand. The Sn2+ doping enhances the emission quantum yield from 35% to 63% and dramatically improves the colloidal and phase stability. Also, we demonstrated the use of Sn doped FAPbI3 NCs in near-infrared (NIR) LEDs.